The Evaluation of Education Quality Assurance at ‎ SD N Noborejo 01 Using CIPP - Budi Yuwono Dwimurtiyanto (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
This research is aimed at evaluating the implementation of education quality assurance program at SD N Noborejo 01 using Context, Input, Process, Product (CIPP) model which used evaluation approach using descriptive qualitative method. The research result shows that based on the context evaluation, it has not met the minimal standard of internal quality assurance system set by the government. According to the evaluation result, external quality assurance system is categorized into standard “A” which includes standard of education, teacher and staf, and scoring management that are involved into good category. The aspects of process consist of content standard, process standard, and evaluation standard which are included into good category. In the aspect of product standard category, the passing grade is assesed and results good category. The impact of education quality assurance evaluation at SD N Noborejo 01 are: 1) Output: SD N Noborejo 01 is able to implement the whole cycle of CIIP model and the effectiveness of education quality assurance organization at school; 2) Outcome: the learning process has been implemented based on standard; 3) Impact: the quality culture of SD N Noborejo 01 has been constructed and learning outcome quality has increased.